2005
DOI: 10.1111/j.1475-6773.2005.00350.x
|View full text |Cite
|
Sign up to set email alerts
|

Response Rates and Response Bias for 50 Surveys of Pediatricians

Abstract: Research Objective. To track response rates across time for surveys of pediatricians, to explore whether response bias is present for these surveys, and to examine whether response bias increases with lower response rates. Data Source/Study Setting. A total of 63,473 cases were gathered from 50 different surveys of pediatricians conducted by the American Academy of Pediatrics (AAP) since 1994. Thirty-one surveys targeted active U.S. members of the AAP, six targeted pediatric residents, and the remaining 13 tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

36
251
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(298 citation statements)
references
References 45 publications
36
251
8
Order By: Relevance
“…Also, since the response rate was only 53%, attitudes and perceptions of non-respondents may have differed from respondents. But, although some non-response bias was found with females being more likely to respond to the survey, this tendency is consistent with previous AAP surveys where the non-response bias was examined and found to be minimal [38]. Finally, results from this study are based on AAP membership, which constitutes a large subset but not all U.S. pediatricians and no family physicians.…”
Section: Discussionsupporting
confidence: 88%
“…Also, since the response rate was only 53%, attitudes and perceptions of non-respondents may have differed from respondents. But, although some non-response bias was found with females being more likely to respond to the survey, this tendency is consistent with previous AAP surveys where the non-response bias was examined and found to be minimal [38]. Finally, results from this study are based on AAP membership, which constitutes a large subset but not all U.S. pediatricians and no family physicians.…”
Section: Discussionsupporting
confidence: 88%
“…Second, as there is no available information about the characteristics of non-responders, it is not possible to determine whether those who did respond were demographically or professionally distinctive in some way. However, other studies have found that low response rates in surveys of healthcare professionals only minimally increase the risk of response bias (Cull et al 2005). In addition, our results correspond with findings from other jurisdictions relating to both knowledge (e.g.…”
Section: Study Strengths and Limitationssupporting
confidence: 82%
“…The response rate we observed is comparable to reported response rates from other Web-based surveys of physicians and surveys involving neonatologists [7,15,36]. Response rates for physician surveys are on average more than 10% lower than those for nonphysician surveys and have declined during the past decade [3,11]. Due to limited resources, we were not able to employ multiple Because variations in practice attitudes that are due to insufficient evidence may have important implications for long-term outcomes of these vulnerable premature infants, there is a need to conduct studies on the use of multiple courses of indomethacin for PDA closure and the use of indomethacin for reopened PDA beyond the first 2 weeks.…”
supporting
confidence: 78%
“…We did not solicit identifying information from the participants per institutional review board policies for exempt research, and therefore we were not able to target nonresponders. Previous studies of nonresponse to pediatrician surveys have found that low response rates are not necessarily an indicator of response bias [11].…”
Section: Discussionmentioning
confidence: 99%